Polymorphisms within the human leucocyte antigen-E gene and their associations with susceptibility to rheumatoid arthritis as well as clinical outcome of anti-tumour necrosis factor therapy. (28th September 2015) - Iwaszko, M; Świerkot, J; Kolossa, K; Jeka, S; Wiland, P; Bogunia-Kubik, K
Summary: Involvement of the non-classical human leucocyte antigen-E (HLA-E) in both innate and acquired immune response suggests its possible role in development of autoimmune pathologies. This study was undertaken to investigate relationships between the HLA-E gene single nucleotide polymorphisms (SNPs) and a risk of rheumatoid arthritis (RA), as well as to evaluate a potential of these polymorphisms to modulate clinical outcome of anti-tumour necrosis factor (TNF) treatment in female patients. A total of 223 female patients with RA receiving anti-TNF biological therapy and 134 female healthy subjects were enrolled into the study. Genotypings for two SNPs within the HLA-E gene (rs1264457 HLA-E*01:01/01:03; rs1059510 HLA-E*01:03:01/01:03:02) were performed using a polymerase chain reaction (PCR) amplification employing LightSNiP assays. Clinical response was evaluated according to the European League Against Rheumatism (EULAR) criteria at 12 and 24 weeks after initiation of the therapy. The frequency of the HLA-E*01:01/01:01 genotype was decreased significantly in RA patients in comparison to controls ( P = 0·031). The presence of the HLA-E*01:01/01:01 genotype in patients correlated with better EULAR response after 12 weeks of anti-TNF treatment, while 01:03 allele carriers were generally unresponsive to the treatment ( P = 0·014). The HLA-E*01:03/01:03 genotype was also over-represented among non-responding patients in comparison to HLA-E*01:01/01:01 homozygotes ( P = 0·021). With respect to the HLA-E rs1059510 variation, a better response after 12 weeks was observed more frequently in patients carrying the HLA-E*01:03:01/01:03:01 genotype than other genotypes ( P = 0·009). The results derived from this study imply that HLA-E polymorphisms may influence RA susceptibility and affect clinical outcome of anti-TNF therapy in female RA patients.